3D - RECURSIVELY SCANS IMAGING SYSTEM WITH COMPUTER MATHEMATICS - Lazurchak, І.І. (Journal of Information Technologies in Education (ITE), 2014)
In this paper the algorithm for constructing the N-dimensional recursive Peano scans. Driven by their two-dimensional and three-dimensional realization of a system of computer mathematics Mathematica 7.0. We are discussing the issue of reduction of the multidimensional space to onedimensional in the calculation of multiple integrals.